ANALISIS TINGKAT PENCEMARAN UDARA DI TERMINAL KOTA SEMARANG - Dhita Ayu Fauziah; Mursid Rahadjo; Nikie Astorina Yunita Dewanti (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Transport is a major source of air pollution. PM10 is a pollutant which is a health predictor and can cause vital pulmonary damage. Terminal is one of the high locations of air pollution due to the activity of motor vehicles. This study aims to measure the level of air pollution and the relationship between inhaled dust levels and vital capacity of lung at Semarang City Terminal. The type of research is observational analytic research with cross sectional approach. The population in this study is the air in Semarang City Terminal and 76 traders. The sample of this research is PM10 at 1 point on the three terminals with the number of respondents as many as 30 traders using purposive random sampling. The results of laboratory PM10 ambient air in Semarang City terminal is in the range 38.39 - 99.35 μg/m3 and the inhaled dust levels of traders are in the range 0.83 - 3.33 mg/m3. Measuring the pulmonary vital instrument of traders shows the normal results of 13 traders and 17 traders are not normal. The results of the research with Chi Square test showed that the association of inhaled dust content with vital capacity of lung (p = 0,024) and the presence of inhaled dust levels exceeding NAB (3 mg / m3) was an abnormal lung vital capacity risk factor (RP = 2.18) . The air quality in Semarang City Terminal is in good and medium category and there is correlation of inhaled dust level with vital capacity of lung at permanent traders at Semarang City Terminal.